Cardiovascular Disease Risk Among Older Immigrants in the United States: A Comparison of Risk Measures. Issue 6 (November 2018) - Sadarangani, Tina R.; Chyun, Deborah; Trinh-Shevrin, Chau; Yu, Gary; Kovner, Christine
Abstract : Background: In the United States, 16 million immigrants are 50 years and older, but little is known about their cardiometabolic health and how to best assess their cardiovascular disease (CVD) risk. Aging immigrants may therefore not be benefitting from advances in CVD prevention. Objective: In this study, we estimate and compare CVD risk in a nationally representative sample of aging immigrants using 3 different measures. Methods: This was a cross-sectional analysis using National Health and Nutrition Examination Survey data. Immigrants 50 years and older with no history of CVD were eligible. The Framingham Risk Score (FRS), the American College of Cardiology/American Heart Association Pooled Cohort Risk Equation, and presence of metabolic syndrome (MetS) were used to estimate risk. Bivariate statistics were analyzed using SPSS version 23.0 Complex Survey module to account for National Health and Nutrition Examination Survey unique weighting scheme. Results: The mean age of the sample was 61.3 years; 40% had hypertension, 17% had diabetes, 10% were smokers, and 95% did not meet the recommended physical activity guidelines. Proportions at an elevated CVD risk were as follows: American College of Cardiology/American Heart Association, 42% female and 76% male; FRS, 17.4% female and 76% male; and MetS, 22% female and 24% male. Conclusions: Immigrants had a lower overall risk using MetS and the American College of Cardiology/American Heart Association equation than has been found using these tools in similarly aged samples. The opposite was true for the FRS. The discrepancy between the proportion at risk and those being treated may reflect healthcare access gaps that warrant further investigation. A more holistic approach to risk measurement is needed that accounts for determinants of health that disproportionately affect immigrants, including language and socioeconomic status.